2020
DOI: 10.3390/foods10010012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Xanthan and Locust Bean Gum in a Gluten-Free Infant Biscuit Based on Rice-Chickpea Flour Using Response Surface Methodology

Abstract: Incorporation of xanthan gum and locust bean gum in rice flour supplemented by chickpea flour was used to obtain a good quality of nutritionally enriched biscuit for celiac children. Response surface methodology (RSM) was applied to optimize the levels of xanthan and locust bean gum added to the composite gluten-free flour. Analysis was based on the rheological (hardness and viscoelastic) characteristics of the dough and specific volume, water activity, and hardness of the biscuit. The results revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The results in Table 6 showed that adding carob bean gum to the gluten-free bread at 0.5, 1.0, and 1.5% had no p ≥0.05 effects on the nutritional quality or the values of protein, fat, ash, ber, total carbohydrates, or energy, in compared to the control. That is because carob bean gum acts as a binding agent or a substitute for gluten in gluten-free bread formulations based on corn starch with an improvement in the nal texture and adds viscosity to the dough, with no effects on the nutritional quality of these bread formulations 3,14,34].…”
Section: Nutritional Quality Of Cupcakes and Gluten-free Breadmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Table 6 showed that adding carob bean gum to the gluten-free bread at 0.5, 1.0, and 1.5% had no p ≥0.05 effects on the nutritional quality or the values of protein, fat, ash, ber, total carbohydrates, or energy, in compared to the control. That is because carob bean gum acts as a binding agent or a substitute for gluten in gluten-free bread formulations based on corn starch with an improvement in the nal texture and adds viscosity to the dough, with no effects on the nutritional quality of these bread formulations 3,14,34].…”
Section: Nutritional Quality Of Cupcakes and Gluten-free Breadmentioning
confidence: 99%
“…For that, carob seeds are used to produce Locust Bean Gum (LBG), which could be used as a thickener, hydrocolloid, stabilizer, emulsi er, and gelling agent in the food industry, and is approved in most areas of the world; chemically known as E410 to mimic the viscoelastic properties of gluten to improve dough handling and to improve the overall quality of nished baked products. LBG is characterized by biodegradability, low toxicity, and low cost contributing to its signi cant utilization in various products [4,14].Accordingly, the present research work aimed to (i) utilize the roasted carob powder from the pulp (130° C/ 30 min) as a natural sweetener in replacement with cane sugar at 0, 25, 50, and 75% in cacao cupcakes formula; (ii) utilize carob bean gum from seeds as a by-product of pods in gluten-free bread at 0, 0.5, 1.0 and 1.5 %, (iii) assess the chemical, viscosity and antioxidant properties of the raw materials, (iv) evaluate the sensory, physicochemical and texture properties of the produced cupcakes and gluten-free bread.…”
mentioning
confidence: 99%
“…In another study, rice flour with potato starch and locust bean gum as gluten-free ingredients were used in baked products [ 9 ]. Moreover, other gluten-free ingredients, including maize [ 10 ], oat [ 11 ], sweet potato [ 12 ], water chestnut [ 13 ], peanut-pearl millet composite [ 14 ], and even infant biscuit formulas containing rice and chickpea flours [ 15 ], were studied by researchers to learn more about the desirability of food selection among the various classes of consumers [ 15 ]. In the present study, rice flour is used as the major ingredient for the preparation of gluten-free biscuits for a desirable palatable feel [ 16 ], whereas the studies mentioned above utilized pseudocereal and legume flours in the manufacturing of gluten-free biscuits, which can only partially fulfill the desire of satiety.…”
Section: Introductionmentioning
confidence: 99%
“…Rice starch (RS) products are common diets in China and Southeast Asian countries due to the consumer-friendly taste, texture, and ease-of-preparation feature [ 1 , 2 ]. RS products are also an important alternative diet for patients with celiac disease [ 3 ]. However, RS gels have deficiencies in ductility, elasticity, and extensibility in the processing and texture of products [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%